Enhancing radiation safety and efficiency in nuclear medicine through automated drug dispensing systems: A feasibility study with staff acceptance analysis - Sanoop Chandran, Annamalai Rama, Induja Govindan, Anjana A. Kailas, Srinivas Hebbar, Anup Naha, Usha Rani (Journal of Applied Pharmaceutical Science, 2024)
Nuclear medicine, a vital component of modern healthcare, harnesses the power of radioactive isotopes to enable precise diagnoses and treatments. However, the handling of radioactive materials poses inherent risks. This study introduces an automated drug dispensing system (ADDS) within a nuclear medicine department to enhance safety and efficiency. The research comprehensively evaluates ADDS implementation’s financial and operational feasibility, considering staff perceptions and acceptance. Findings reveal that RESCUEDOSE, an ADDS solution, offers a cost-effective, safety-enhancing option with rapid investment returns. Staff members exhibit favorable acceptance, contingent on adequate training. This study contributes to the broader trend of automation in healthcare, emphasizing its potential to elevate patient care and radiation safety.
Keywords: Nuclear medicine, automated drug dispensing system (ADDS), radiation safety, radiopharmaceuticals, financial feasibility, staff acceptance